2011
DOI: 10.1016/j.ejvs.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Revascularisation with Silver-coated Polyester Prostheses and Arterial Homografts in Patients with Aortic Graft Infection – A Prospective, Comparative, Single-centre Study

Abstract: Our study suggests that silver-coated prostheses can be as effective as arterial allografts in the treatment of infections of vascular prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 21 publications
0
13
0
5
Order By: Relevance
“…70,103,109,110 As with rifampin-bonded grafts, reinfection rates were higher with silver-coated grafts than with the use of cryopreserved arterial homografts. The major advantages of rifampin-bonded or silver-coated synthetic grafts were lower amputation rates, fewer conduit failures, lower earlier mortality rates, and the fact that they can be used in emergency surgery.…”
Section: Graft Excision and In Situ Reconstructionmentioning
confidence: 99%
See 2 more Smart Citations
“…70,103,109,110 As with rifampin-bonded grafts, reinfection rates were higher with silver-coated grafts than with the use of cryopreserved arterial homografts. The major advantages of rifampin-bonded or silver-coated synthetic grafts were lower amputation rates, fewer conduit failures, lower earlier mortality rates, and the fact that they can be used in emergency surgery.…”
Section: Graft Excision and In Situ Reconstructionmentioning
confidence: 99%
“…A potential disadvantage of rifampin-bonded prosthesis is the development of rifampin resistance, which is not a concern with silver-coated synthetic grafts. 3,70,109,110 Bandyk et al 14 and O'Connor et al 4 suggested that rifampin-bonded or silver-coated grafts should be considered for patients with infection caused by less virulent microorganisms, such as coagulase-negative staphylococci or streptococci. These authors suggested that rifampin-bonded synthetic grafts should not be used in patients with aortoenteric fistulae or in infections caused by MRSA or Pseudomonas or with extensive perigraft abscess because of the risk of reinfection.…”
Section: Graft Excision and In Situ Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Несомненным пре-имуществом импрегнированных серебром протезов явля-ется их готовность к использованию сразу после вскрытия упаковки (нет необходимости замачивания в растворе антибиотика или антисептика), аналогичные неимпрег-нированным графтам плотность, прочность, отсутствие выраженной тканевой реакции и в первую очередь анти-микробные качества [21,[23][24][25]. Ряд исследователей [26][27][28][29][30][31] считают возможным использовать их даже в ин-фекционном очаге в позиции in situ, указывая на результа-ты, схожие с использованием алло-или аутовенозных графтов. Основным аргументом скептически настроенных ис-следователей становится отсутствие таких данных о нали-чии и выраженности антибактериальной активности этих протезов, которые бы не вызывали сомнений в своей до-стоверности.…”
Section: Discussionunclassified
“…In the setting of infection, surgical explantation carries a mortality of 18-30% [12]. Revascularization is performed via extra-anatomic routes, however, in situ revascularization with autologous femoral vein or rifampinsoaked grafts is another viable option [14,28]. Regardless of the method of revascularization, expeditious diagnosis and treatment is paramount to patient survival.…”
Section: Treatment and Outcomesmentioning
confidence: 99%